TATALAKSANA PEMELIHARAAN AYAM RAS PETELUR PERIODE LAYER DI POPULER FARM DESA KUNCEN KECAMATAN MIJEN KOTA SEMARANG - Nurcholis Nurcholis; Dewi Hastuti; Barep Sutiono (Universitas Wahid Hasyim, 2009)
Report compiled to executed Field in Popular Farm Country Kuncen District Mijen Town Semarang to obtain;get knowledge, ability and skilled about management conservancy of petelur race chicken specially layer period. Used items Farm owning layer chicken counted 47.630 tail, what consist of two strain that is New Lohman Platinum and Isa Brown. Used by Method is to 1) conducting all routine activity 2) doing record-keeping of done data with interview, direct perception, activity note and also recording company of ranch. Data in field indicate that cage building in Popular Farm most of all using W type, what aim to be can load more population. passed to feed chicken represent result from mixing alone which is based to the protein content with rate 18% per ton for the period of Grower and 19% per ton for the period of Layer. Giving of Feed, twice one day that is morning at 08.00 WIB counted 50% and daytime at 13.00 WIB counted 50%. Drinking water given ad libitum. Place feed form is